2015
DOI: 10.33549/physiolres.933210
|View full text |Cite
|
Sign up to set email alerts
|

OPRM1 and ABCB1 Polymorphisms and Their Effect on Postoperative Pain Relief With Piritramide

Abstract: Genetic factors may contribute to the differential response to opioids. The aim of this study was to evaluate the association between polymorphisms of µ1-opioid receptor gene OPRM1 (rs1799971), and P-glycoprotein transporter gene ABCB1 (rs1045642, rs2032582), and piritramide efficacy under postoperative patient-controlled analgesia (PCA). In 51 patients, OPRM1 variant was associated with decreased efficacy in early postoperative period evidenced by sum of pain intensity difference in the 0-6 h postoperative pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
1
11
1
Order By: Relevance
“…44 To our knowledge, rs677830 and rs5885589 have not been reported as causal polymorphisms. Interactions between these loci, or others, may be responsible for compensation when a damaging polymorphism dramatically alters normal protein activity, as suggested by Bartošová et al 56 and Barratt et al 57 with ABCB1 and OPRM1 polymorphisms shown to alter protein activity in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…44 To our knowledge, rs677830 and rs5885589 have not been reported as causal polymorphisms. Interactions between these loci, or others, may be responsible for compensation when a damaging polymorphism dramatically alters normal protein activity, as suggested by Bartošová et al 56 and Barratt et al 57 with ABCB1 and OPRM1 polymorphisms shown to alter protein activity in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…This study is based on the hypothesis that patients with polymorphisms in OPRM1 and COMT have differences in the levels of perception and modulation of pain, since carriers of these polymorphisms exhibit different affinities for the binding sites of their receptors, which determines different analgesic capacities (Bartošová et al, 2015), according to the endogenous ligand that is coupled to these receptors. Therefore, people with these polymorphisms may have different perceptions of pain when treated with opioids.…”
Section: Discussionmentioning
confidence: 99%
“…The most common SNP studied in OPRM1 is rs1799971, referred to as A118G (Matsunaga et al, 2009;Crist and Berrettini, 2014). When treated with opioids, or rescue medication, individuals with the G allele have more pain symptoms than individuals without the G allele, and thus have increased adverse effects, such as those demonstrated in studies evaluating orthopedic surgeries (Bond et al, 1998;Bartošová et al, 2015). In our study, the frequency of OPRM1 haplotypes was similar to the ratio reported previously, where, among the 200 volunteers, 69.5% were A/A, 25.5% were A/G and 2.5% were G/G (Trescot et al, 2008;Liu and Wang, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, in highs the expectation of pain relief does not totally account for the suggestion induced analgesia (Gearan and Kirsch, 1993 ) and it is unlikely that the expectation of analgesia could be sustained by opioid mechanisms, in contrast to the general population (Amanzio and Benedetti, 1999 ; Benedetti et al, 1999 ; Petrovic et al, 2002 ; Zubieta et al, 2005 ; Scott et al, 2008 ; Babel et al, 2017 ). In fact, not only the effects of suggestions is not abolished by naloxone (Moret et al, 1991 ) but, in addition, highs display the μ1 polymorphism (Presciuttini et al, 2018 ) which has been found associated with low sensitivity to opiates, low placebo response (Trescot and Faynboym, 2014 ; Bartošová et al, 2015 ; Peciña and Zubieta, 2015 ) and larger opiates consumption for post-surgery (Zhang et al, 2005 ; Boswell et al, 2013 ; Sia et al, 2013 ; Ren et al, 2015 ) and cancer pain (Gong et al, 2013 ; Wan et al, 2015 ; Yao et al, 2015 ).…”
Section: Hypnotizability and Expectation Of Pain Reliefmentioning
confidence: 99%